Strong terahertz generation by optical rectification of a super-Gaussian laser beam. (27th June 2016) - Kumar, Subodh; Singh, Ram Kishor; Sharma, R. P.
Abstract: Terahertz (THz) generation by optical rectification of a laser beam having spatially super-Gaussian and temporally Gaussian intensity profile is investigated when it is propagating in a pre-formed rippled density plasma. The quasi-static ponderomotive force which is generated due to the variation in intensity of laser pulse leads to a nonlinear current density in the direction transverse to the direction of propagation which drives a radiation. The frequency of this radiation falls in the THz range if the pulse duration of the laser is chosen suitably. The density ripple provides the phase matching. The yield of generated THz has been compared when the phase matching is exact and when there is slight mismatch of phases. The variation in the intensity of the generated THz with the index of super-Gaussian pulse has also been studied.